Rekonstruksi Pengelolaan Sumber Daya Pesisir dan Laut Berdasarkan Tujuh Pilar: Upaya Mengatasi Kompleksitas Hukum dan Kewenangan di Era Desentralisasi - Tripanji Aryawardhana; Lazarus Tri Setyawanta; Lita Tyesta Addy Listya Wardhani (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2025)
The complexity of coastal and marine resource management in Indonesia is often caused by overlapping authorities between institutions and sectoral regulatory disharmony. This phenomenon has resulted in legal uncertainty, marginalization of coastal communities, and marine environmental damage. The research aims to reconstruct a governance model that promotes legal certainty, justice, and sustainability. Using a normative legal research method supported by statutory, conceptual, case, and historical approaches, this article analyzes the distribution of authority and its implications for coastal governance in the post-decentralization era. The findings reveal that the withdrawal of maritime authority from districts to provinces has created administrative gaps, weakened local participation, and increased legal uncertainty. This article offers a reconstructive approach based on seven pillars that integrate the principles of the rule of law, balance between central and regional relations, revitalization of assistance tasks, internalization of Pancasila values of justice, strengthening of local institutions, utilization of Geographic Information System (GIS) technology, and mainstreaming of ecological awareness and legal spirituality. Using a normative legal approach, this article argues that the seven pillars constitute a conceptual and operational framework for restructuring a coastal resource management system that is equitable, effective, and sustainable.